2001
DOI: 10.1152/ajpheart.2001.281.5.h1992
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-conditioned medium increases endothelial electrical resistance independently of cAMP/PKA and cGMP/PKG

Abstract: Platelets release a soluble factor into blood and conditioned medium (PCM) that decreases vascular endothelial permeability. The objective of this study was to determine the signal-transduction pathway that elicits this decrease in permeability. Permeability-decreasing activity of PCM was assessed by the real-time measurement of electrical resistance across cell monolayers derived from bovine pulmonary arteries and microvessels. Using a desensitization protocol with cAMP/protein kinase A (PKA)-enhancing agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…At each frequency, the statistics of 64 voltage measurements sampled at a rate of 32 Hz for 2 s were evaluated using Eqs. (9)(10)(11). The electrode circuit model frequency-dependent average voltages are in qualitative agreement with those of the gold electrode.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…At each frequency, the statistics of 64 voltage measurements sampled at a rate of 32 Hz for 2 s were evaluated using Eqs. (9)(10)(11). The electrode circuit model frequency-dependent average voltages are in qualitative agreement with those of the gold electrode.…”
Section: Resultssupporting
confidence: 53%
“…One of the most common microimpedance sensors currently available consists of a gold micro-electrode with a large counter electrode. 12,13 Although such sensors have been increasingly used to probe and study time-and frequency-dependent cellular impedances, 1,4,[6][7][8]11,18,[20][21][22][23]25,[27][28][29] several forms of random and systematic errors may potentially corrupt these impedance measurements. Despite the importance of this technology, few studies have attempted to identify and reduce these errors and their propagation into cellular barrier function parameter estimates based on cell-cell, cell-matrix, and membrane impedance components.…”
Section: Introductionmentioning
confidence: 99%
“…These observations clearly establish that the platelet, via soluble platelet-derived factors, is essential in maintaining normal vascular homeostasis. We and others have reported on vasoactive plateletderived lipids that activate endothelium, including our first report that S1P activated EC phospholipase D (7,10,23,33,48). Subsequent studies have since demonstrated that platelet-derived phospholipids modulate the barrier function of the vascular endothelium via both endothelial barrier-perturbing lipid products such as phosphatidate (6) and barrier-stabilizing/enhancing lipid products such as lysophosphatidic acid (LPA) (8,32) and S1P (11).…”
Section: Discussionmentioning
confidence: 86%
“…S1P is a normal constituent in plasma with increased (micromolar) levels in serum that are consistent with S1P release during whole blood coagulation (51). S1P exerts diverse biological effects on cells and is now recognized as an important courier of cellular information (7,10,23,33,48). S1P stimulates proliferation, calcium mobilization, adhesion molecule expression, and suppression of caspasedependent apoptosis (7,20,40,46) via ligation of G protein-coupled receptors of the EDG family (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation